2023
DOI: 10.3390/buildings13040917
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Government Policy Combination Prevents Greenwashing in Green Building Projects? An Evolutionary Game Perspective

Abstract: Green buildings (GBs) can effectively reduce building energy consumption and alleviate energy problems. However, as green building projects swell, the development process of GBs in China has gradually exposed many problems, among which the greenwashing behavior of construction enterprises is the more serious. The government needs to adopt some appropriate policies to prevent problems in GBs. This paper uses the evolutionary game theory to construct models and proposes four policy combinations: static reward an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It covers all stages of planning, design, construction, operation and management, demolition, and recycling during that life span and establishes a whole-process building-management system [ 12 , 13 , 15 ]. Green buildings can reduce or eliminate negative impacts on the climate and natural environment in their design, construction, or operation [ 56 , 57 ] and thus have received widespread attention around the world.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…It covers all stages of planning, design, construction, operation and management, demolition, and recycling during that life span and establishes a whole-process building-management system [ 12 , 13 , 15 ]. Green buildings can reduce or eliminate negative impacts on the climate and natural environment in their design, construction, or operation [ 56 , 57 ] and thus have received widespread attention around the world.…”
Section: Institutional Backgroundmentioning
confidence: 99%
“…The model incorporated three policy instruments, namely carbon taxation, solar technology subsidies, and energy efficiency renovation funds. Chen et al [48] employed evolutionary game theory to develop a model and investigated the effects of four policy combinations on construction strategies. Their study analyzed the inherent mechanisms of behavioral evolution for both government agencies and construction enterprises, providing insights into the interactions and dynamics between the two entities in the context of policy implementation.…”
Section: Abstract Clustering Analysismentioning
confidence: 99%
“…Under government reward and punishment mechanisms, administrative measures have a significant impact on promoting green building development. Chen [45] and Meng [13] used a two-player evolutionary game model to study the intrinsic mechanisms of government and construction enterprise behavior evolution. The results indicated that the combination of dynamic subsidies and static penalties achieved the best outcomes for promoting green construction by enterprises.…”
Section: Study On Green Finance In Green Buildingsmentioning
confidence: 99%